2008
DOI: 10.1080/15563650802304419
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ethyl pyruvate on dapsone-induced methemoglobinemia in rats

Abstract: A single intraperitoneal dose of EP was able to reduce methemoglobinemia induced by dapsone for a short period of time, but this effect was not sustained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Pyruvate is an effective scavenger of the ROS, hydrogen peroxide, and hydroxyl radical [27][28][29]. EP is also an effective ROS scavenger, as evidenced by studies showing that EP inhibits hepatic lipid peroxidation induced by hemorrhagic shock in rats [12], methemoglobin formation induced by dapsone ingestion in rats [30], testicular lipid peroxidation in rats subjected to testicular I/R injury [31], and ileal lipid peroxidation in rats subjected to cutaneous burn injury [6]. In the present study, all four compounds studied, namely pyruvate, EP, BF, and PHPP, ameliorated hepatic lipid peroxidation induced by transient aortic occlusion.…”
Section: Discussionmentioning
confidence: 94%
“…Pyruvate is an effective scavenger of the ROS, hydrogen peroxide, and hydroxyl radical [27][28][29]. EP is also an effective ROS scavenger, as evidenced by studies showing that EP inhibits hepatic lipid peroxidation induced by hemorrhagic shock in rats [12], methemoglobin formation induced by dapsone ingestion in rats [30], testicular lipid peroxidation in rats subjected to testicular I/R injury [31], and ileal lipid peroxidation in rats subjected to cutaneous burn injury [6]. In the present study, all four compounds studied, namely pyruvate, EP, BF, and PHPP, ameliorated hepatic lipid peroxidation induced by transient aortic occlusion.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, it has been reported that antioxidants can prevent the progress of pulmonary fibrosis (Suntres, 2002;Jo et al, 2008). The commonly used drugs include vitamin C, vitamin E, ambroxol, glutathione, and n-acetylcysteine (Moon and Chun, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…34 Notably, the beneficial effects of 100 mg/kg ethyl pyruvate were superior compared to those of 50 mg/kg, which are consistent with our dose-response results ( Figure S1). A single intraperitoneal dose of ethyl pyruvate was able to reduce methaemoglobinaemia induced by dapsone for a short period of time of 3-6 h. 56 Thus, a second dose was designed to be given after the mice subjected to 4 hours of MV at our protocol. As for the toxicity of ethyl pyruvate, dosage up to 150 mg/kg was proven to be a safe and effective medication in endotoxaemic horses, and ethyl pyruvate (90 mg/kg) at 6-hour intervals for five more doses was used with safety in human trials.…”
Section: Discussionmentioning
confidence: 99%